A regional multidisciplinary network enhances child abuse case management. Issue 1 (20th July 2022) - Watanabe, Yoshihiro; Shiga, Kentaro; Kikuchi, Nobuyuki; Kurihara, Yachiyo; Sato, Atsuo
Abstract: Background: We previously reported an inadequate response to intracranial hemorrhage (ICH) cases under 24 months of age in Yokohama from 2011 to 2013. Hence, it is very important to evaluate how the establishment of a regional multidisciplinary network for child abuse affects the response to ICH cases in medical institutions. Methods: We conducted a questionnaire survey of ICH cases under 24 months of age from 2014 to 2016 using a regional multidisciplinary network for child abuse established in Yokohama in September 2013. We investigated the patients' characteristics, examinations to identify inflicted injury, and reports made to the hospital‐based child protection team (CPT) or regional child protective service (CPS), and compared the results of a previous study and the current study, which corresponds to before and after the establishment of the regional network, respectively. Results: The total number of ICH cases was 50 in 3 years. The number of cases surveyed for covert fracture and fundus hemorrhage increased significantly after the establishment of the regional network ( P = 0.0001 and P = 0.0182, respectively). The number of cases reported as suspected child abuse was 41 (82%) to the hospital‐based CPTs and 27 (54%) to the regional CPSs. There were significant differences between before and after the establishment of the regional network regarding CPT ( P = 0.0062) and CPS ( P = 0.0215) reports. Conclusions: A regional multidisciplinary network can enhance response and cooperation to address child abuse. It deepens our understanding of such care and improves awareness by hospital personnel of child abuse.